Current Obstetrics and Gynecology Reports - McElrath, Thomas F.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal aims to provide expert review articles on significant recent developments in obstetrics and gynecology. Presented in clear, insightful, balanced contributions by international experts, the journal intends to serve all those involved in the diagnosis, treatment, management, and prevention of conditions that compromise the health of women. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas, such as endometriosis, infertility, menopause, prenatal medicine, and vulval and cervical lesions. Section Editors select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An Editorial Board of nearly 20 international members reviews the annual table of contents, suggests articles of special importance to their country/region, and ensures that topics include emerging research. Commentaries from well-known figures in the field are also provided.
Keywords: Medicine; Obstetrics; Maternal and child health services; Oncology; Obstetrics/Perinatology/Midwifery.; Maternal and Child Health; Medicine/Public Health, general; Oncology